Leveraging new business innovation for strategic renewal: An organizational framework for strategic corporate venturing - Lysander Weiss; Dominik K. Kanbach (Creativity and Innovation Management, 2023)
To adapt their competitive advantages for successful strategic renewal, established companies must apply suitable innovation activities. One way to achieve this is the establishment of corporate venturing units that create organizationally consequential new business innovation for their parent company. However, the understanding of the distinctive organizational characteristics for such strategic corporate venturing is limited. To address this gap, our abductive study develops a conceptual organizational framework by linking key concepts of strategic renewal with corporate venturing. This framework is subsequently compared with insights emerging from the qualitative data of 29 corporate venturing units. This comparison allows us to define six types of units with different possible roles for the strategic renewal of the parent company, and a final exploratory organizational framework with distinctive organizational characteristics for strategic corporate venturing. These include a set of dynamic capabilities with corresponding resources as possible enablers for a planned innovation logic that requires interlinked-ambidextrous structures. These findings provide a foundation for an empirical model of strategic corporate venturing, as well as novel insights for establishing dynamic capabilities and ambidexterity within interlinked organizational entities. Practitioners can build on these findings to leverage corporate venturing units as a systematic and organized innovation activity for strategic renewal.
Keywords: 330; continuous innovation; corporate innovation; corporate venturing; corporate venturing units; dynamic capabilities; innovation management; new business innovation; organizational ambidexterity; strategic corporate venturing; strategic renewal